Necrotizing soft-tissue infections - Sutherland, M E; Meyer, A A (The Surgical clinics of North America, 1994)
In the realm of clinical practice, this disease entity defies applicability to any classification scheme. Of paramount importance is the early identification of all necrotizing soft-tissue infections. This requires a high index of suspicion, aided by recognition of various risk factors and organ system dysfunction out of proportion to the extent of local signs and symptoms. Expedient, aggressive surgical therapy is imperative: resuscitation, wide débridement, and antibiotic therapy. Once the infection has been controlled, continued supportive care, reconstruction, and rehabilitation can proceed.